Au‐Coated Honeycomb Structure as an Efficient TCO‐Free Counter‐Electrode for Quantum‐Dot‐Sensitized Solar Cells. Issue 3 (14th December 2017) - Dao, Van‐Duong; Bui, Van‐Tien; Baek, Minki; Phan, The‐Long; Yong, Kijung; Choi, Ho‐Suk
Abstract: This study reports the fabrication of a Petri dish patterned with cylindrical micro‐cavities that are produced using a one‐step solvent‐immersion phase‐separation process. The developed 3D honeycomb Petri dish is coated with a Au film through a sputtering method to be an efficient Au‐coated FTO‐free electrode for quantum‐dot‐sensitized solar cells. Due to the high specific active surface area of the electrode with the Au‐coated honeycomb structure, the energy conversion efficiency of devices that use this electrode is 5.2 % compared to 4.4 and 4.7 % by devices using an Au‐coated flat Petri dish and an Au‐coated FTO electrode, respectively. This design strategy offers excellent potential for the fabrication of highly efficient counter electrodes with FTO‐free substrates of flexible photovoltaic devices. Abstract : The power of honeycomb : A Petri dish patterned with cylindrical micro‐cavity is produced using a one‐step solvent‐immersion phase‐separation process as an efficient template for fabricating Au‐coated FTO‐free electrode in quantum‐dot‐sensitized solar cells.